Heritability of time preference: Evidence from German twin data - Philipp Hübler (Universität Augsburg, Institut für Volkswirtschaftslehre, 2017)
Intergenerational correlations of time preference are well documented. However, there is still limited empirical evidence about the role of genetics in this transmission process. In our paper, we use data on roughly 3,000 twins from the German TwinLife project to estimate the heritability of time preference. We rely on an experimentally validated survey measure of temporal discounting, namely, self-assessed patience. The analysis of monozygotic and dizygotic twins enables us to apply standard biometric models. We find that genetic differences explain up to 23 percent of individual variation in patience. Whereas the additive genetic effect and common environmental effects are of minor importance, a major dominant genetic effect is present. These results indicate a notable degree of genetic influence on economic time preferences.
urn:nbn:de:bvb:384-opus4-710695
Keywords: D10; D90; J10; Z10; 330; Twin study; genetics; heritability; patience; time preference